2020
DOI: 10.1002/bjs.11318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative complications on disease recurrence and long-term survival following oesophagogastric cancer resection

Abstract: Background: Postoperative complications after resection of oesophagogastric carcinoma can result in considerable early morbidity and mortality. However, the long-term effects on survival are less clear. Methods: All patients undergoing intentionally curative resection for oesophageal or gastric cancer between 2006 and 2016 were selected from an institutional database. Patients were categorized by complication severity according to the Clavien-Dindo classification (grades 0-V). Complications were defined accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…In this study, the incidence of POI was 20.6%, which is comparable to previous findings [ 17 , 18 ]. The multivariable regression analysis of this retrospective study showed that length of stay, albumin, intraoperative bleeding, and perioperative blood transfusion were independent factors of POI.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the incidence of POI was 20.6%, which is comparable to previous findings [ 17 , 18 ]. The multivariable regression analysis of this retrospective study showed that length of stay, albumin, intraoperative bleeding, and perioperative blood transfusion were independent factors of POI.…”
Section: Discussionsupporting
confidence: 91%
“…Leakage associated with grade III–V complications, according to the Clavien–Dindo grading system 16,17 , was defined as severe AL, and that associated with less severe complications (grade I–II) as non‐severe AL. All patients who died within 30 days of surgery were excluded from the adjusted analyses of long‐term survival, consistent with previous studies 9,18 .…”
Section: Methodsmentioning
confidence: 89%
“…Previous reports on the mechanism of postoperative complications negatively affecting the prognosis of patients with malignant tumors have been inconsistent. JH Saunders et al found that postoperative anastomotic leakage did not affect the long-term survival of patients with esophageal cancer, but other serious complications (except for anastomotic leakage) were identi ed as independent prognostic factors for overall survival and diseasefree survival [25]. In the eld of GC, Masanori et al found in the JCOG1001 study that, regardless of the type or degree of complications after radical GC, postoperative complications were associated with poor OS [26].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of scholars have reported that postoperative complications (PCs) after surgical operations are closely related to the poor prognosis of patients with malignant tumors [23][24][25][26][27]. This retrospective study analyzed this adverse effect and explored whether adjuvant chemotherapy (AC) and the time interval (TI) from radical operation to initiation of adjuvant chemotherapy could abolish the poor prognosis caused by PCs in patients with stage II/III GC.…”
Section: Discussionmentioning
confidence: 99%